Teks Geguritan Darmakaya: Analisis Struktur Dan Fungsi - Rika Aripawan, Kadek; Suardiana, I Wayan; Ngurah Sulibra, I Ketut (Humanis, 2016)
Research on DarmakayaGeguritan text is about the analysis of the structure and function. This analysis has the objective to describe the structure and functions contained in the text GeguritanDarmakaya.                This study uses the theory of structural and function. Structural theory based on the theory of Teeuw and Luxemburg, the function is used from theory Damono , Methods and techniques used is divided into three stages, namely (1) the stage of the provision of data by using the method of literature study and the technique used is the technique of recording, and assisted with translation techniques (2) the stage of data analysis, using qualitative methods and techniques used is descriptive and analytical techniques, and (3) the stage of data analysis using formal methods informally assisted with deductive and inductive techniques.                Disclosure of text structure GeguritanDarmakaya structure forms include; code language and literature, style and variety of language and narrative structure includes; incident, plot, character and characterization, setting, theme and mandate. Functions contained therein, is the function of affirmation, negation function and aesthetic function.